Sustainable Livestock Management Practices: Balancing Productivity and Environmental Health - Kohila, P.; Sumithra, A.; Kumar, G.; Thangadurai, R.; Elamurugan, A.; Ramasamy, M.; Senthilkumar, T.; Malathi, G. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Sustainable livestock management is crucial for ensuring food security, economic viability, and environmental health. The increasing demand for livestock products has intensified the need for practices that enhance productivity while minimizing environmental impacts. This review examines a range of sustainable practices that address these challenges. By emphasizing integrated approaches, the review delves into innovations in feed management, breeding and genetics, waste management, and grazing systems. It explores how optimized diets, alternative feed sources, and precision feeding techniques can improve feed efficiency and reduce greenhouse gas emissions. The role of selective breeding, genetic engineering, and biodiversity conservation in enhancing livestock performance and resilience is also discussed. Waste management practices such as manure composting, anaerobic digestion, and nutrient recycling are evaluated for their effectiveness in reducing pollution and generating renewable energy, grazing and pasture management techniques, including rotational grazing, agroforestry, and silvopasture, are analyzed for their benefits in improving pasture productivity and soil health. The review highlights the significance of technological innovations like precision livestock farming, automation, and biogas production in promoting sustainability, the article underscores the importance of supportive policies, farmer education, and research and development in driving the adoption of sustainable practices. Case studies from different regions illustrate the successful implementation of these strategies and their positive impacts on productivity and environmental health. The review concludes by emphasizing the need for continued collaborative efforts and investments in sustainable livestock management to address the ongoing challenges and opportunities in the sector.